Unionization and Productivity: Evidence from Charter Schools - Cassandra M. D. Hart; Aaron J. Sojourner (Institute for the Study of Labor (IZA), 2014)
This paper studies the relationship between teacher unionization and student achievement. Generally stable patterns of teacher unionization since the 1970s have historically presented challenges in measuring the effects of unionization on educational production. However, the blossoming of the charter school sector in recent decades provides fertile ground for study because while most charters are non-union, teachers at some charters have unionized. Using a generalized difference-in-difference approach combining California union certification data with student achievement data from 2003-2012, we find that, aside from a one-year dip in achievement associated with the unionization process itself, unionization does not affect student achievement.
Keywords: I21; J5; J45; J24; H75; D24; 330; teacher; labor union; student achievement; charter school; education; labor productivity